2014
DOI: 10.1038/onc.2014.389
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic PBX-interacting protein (HPIP) is over expressed in breast infiltrative ductal carcinoma and regulates cell adhesion and migration through modulation of focal adhesion dynamics

Abstract: The scaffolding protein, hematopoietic PBX-interacting protein (HPIP/PBXIP1), regulates cell migration necessary for cancer cell dissemination. However, the mechanism that governs this process remains unknown. We show here that HPIP expression is associated with stages of breast cancer where cell dissemination results in poor patient outcome. Our investigation finds a novel association of HPIP with focal adhesion kinase (FAK) regulating FA dynamics. Interestingly, this interaction that led to activation of FAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Recently, accumulating evidence has revealed that HPIP functions as a promoter of the development and progression of cancers, including breast cancer, 2, 3 astrocytoma, 4 liver cancer, 5, 6 oral cell carcinoma, 7 colorectal cancer 8 and so on. However, the role of HPIP in RCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence has revealed that HPIP functions as a promoter of the development and progression of cancers, including breast cancer, 2, 3 astrocytoma, 4 liver cancer, 5, 6 oral cell carcinoma, 7 colorectal cancer 8 and so on. However, the role of HPIP in RCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HPIP promotes breast cancer cell growth through enhanced estrogen signaling. It also interacts with focal adhesion (FA) complex containing FA kinase (FAK), stimulates FAK, and promotes breast cancer cell migration in a FAK‐dependent manner . Hematopoietic pre‐B cell leukemia transcription factor interacting protein is also overexpressed in liver cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Improved understanding of this deadly cancer at the basic molecular level is particularly needed. Although HPIP has been shown to be involved in the development and progression of several cancers, (10)(11)(12)(13)(14) the importance of HPIP in gastric cancer is still unclear. In this study, we showed for the first time a These findings suggest that HPIP may contribute to gastric carcinogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematopoietic pre-B cell leukemia transcription factor (PBX)-interacting protein (HPIP) is a novel oncogene that is overexpressed in various human cancers, such as non-small-cell lung cancer,4 human spinal glioblastoma,5 thyroid cancer,6 gastric cancer,7 colorectal cancer,8 breast infiltrative ductal carcinoma,9 oral carcinogenesis,10 liver cancer,11 and human melanoma cell 12. Recent studies have demonstrated the multifaceted role of HPIP in pathways associated with cancer progression, including transformation, apoptosis, invasion, and metastasis 4,6,13,14.…”
Section: Introductionmentioning
confidence: 99%